PERSPEKTIF KETIDAKPASTIAN STATUS HUKUM RUMAH SUSUN BUKAN RESIDENSIAL MENURUT UNDANG-UNDANG NOMOR 20 TAHUN 2011 TENTANG RUMAH SUSUN - Rahman, Garry Triargo; Gultom, Elfrida Ratnawati; Rahmawan, Dhany; Indirahati, Novina Sri; Bustani, Simona (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: The elimination of the pure non-residential function of apartment buildings in Apartments Law creates legal uncertainty, leading to issues in certifying the rights of non-residential apartment units, including their legal entity status. The method used is normative, employing secondary data analyzed descriptively with conclusions drawn qualitatively. The legislative gap caused by lawmakers' oversight has led to uncertainty and a lack of legal protection for non-residential apartment buildings without any corrective measures from lawmakers. Consequently, this paper highlights the lawmakers' lack of engagement with stakeholders and apartment building experts, resulting in a focus on residential and mixed-use functions, overlooking the legal reality of pure non-residential apartment buildings that have existed since 1985.Keywords: Legal Status, Apartment, Non-Residential